THEORETICAL DETERMINATION OF TACTICS AS A MILITARY SCIENCE - Petrović, Ivan; Devetak, Saša (The Policy of National Security, 2025)
The development of civilization led to the emergence and growth of countries and armies, whose primary purpose was the country’s defense. This resulted in the development of knowledge related to the methods of conducting armed combat. This knowledge has been systematized over time, and thus, knowledge related to this area, called the art of war, has been created. Since the 19th century, military sciences (tactics, operations, and strategy) have increasingly been considered, replacing the phrase art of war. Since the 19th century, there has been increasing talk of military sciences (tactics, operations, and strategy), which replace the phrase art of war. However, both Eastern and Western directions recognize tactics as a basic military science. However, even today, the theoretical definition of tactics has not been fully completed. Therefore, this paper aims to describe the theoretical determination of tactics as a military science. The first chapter of the paper provides a notional determination of tactics as a military science. The second chapter describes the fundamental constituents of tactics. In the third chapter, a classification of tactics was carried out according to several criteria. The understanding of key terms and the description of the paper’s results were carried out using the following methods: content analysis, definition and classification, historical-comparative methods, analytical-synthetic methods, and deductive methods. The notional determination, description of the constituents, and classification of tactics as a military science represent the result of the paper.